Globalization, neoliberalism and education - de Puelles Benítez, Manuel (Avances en Supervisión Educativa, 2009)
The beginning of one of Ulrich Beck’s latest books, What Is Globalization?, states as follows: "The purpose of this book is to offer a clear and thorough introduction to the hard and hazardous problem of globalization, as well as to assist readers in clarifying its ambiguities of fact and value and in distinguishing its various dimensions more clearly than ever. We will also try to warn against certain misconceptions and how to avoid them, but most of all to broaden horizons for political responses to globalization" (Beck, 1988:11). With this opening, Beck makes clear the difference between globalization as a real phenomenon and the globalization ideology, or Globalism, as referred to by the German sociologist. Unravelling both ideas and studying their influence on Education is the aim of this research paper.